2015
DOI: 10.1038/ejhg.2015.143
|View full text |Cite
|
Sign up to set email alerts
|

Can whole-exome sequencing data be used for linkage analysis?

Abstract: Whole-exome sequencing (WES) has become the strategy of choice to identify causal variants in monogenic disorders. However, the list of candidate variants can be quite large, including false positives generated by sequencing errors. To reduce this list of candidate variants to the most relevant ones, a cost-effective strategy would be to focus on regions of linkage identified through linkage analysis conducted with common polymorphisms present in WES data. However, the non-uniform exon coverage of the genome a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Using real genetic data from three families as an example, Smith et al (35) showed that accurate genetic linkage mapping could be performed with WES SNVs. Gazal et al (36) performed a linkage study of two families with both simulated and real data. They reported similar performances for linkage analyses conducted with GWSA or WES (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using real genetic data from three families as an example, Smith et al (35) showed that accurate genetic linkage mapping could be performed with WES SNVs. Gazal et al (36) performed a linkage study of two families with both simulated and real data. They reported similar performances for linkage analyses conducted with GWSA or WES (36).…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining both WES and GWSA data in patients, kindreds, or populations is DNA-, resource-, and time-consuming. Two studies comparing WES and GWSA in linkage analyses based on real data from three families (35) or both simulated and real data from two families (36) showed that the two sets of genetic data defined linkage peaks (35) and excluded genomic regions (36) in a consistent manner. A recent study estimating homozygosity rates with both GWSA and WES data in patients born to consanguineous families provided recommendations for the detection of homozygous regions by WES (37).…”
mentioning
confidence: 99%
“…The analysis strategy to prioritize candidate variants scored them according to their effect on protein structure and phylogenetic conservation by using a seven-point scoring system (Pathogenic Variant or PAVAR 18 To improve the accuracy of the variant prioritization, we combined the previous results with other bioinformatics tools that include phenotype information such as Exomiser v.2, 21 and Variant Annotation Analysis and Search Tool (VAAST)+Phevor that prioritize the variants and the genes affected using a ranking system. 22,23 We used linkage information derived from the WES-common SNVs within each pedigree to reduce the list of candidate variants, according to the method described by Gazal et al 24 Validation by Sanger sequencing …”
Section: Bioinformatics Analysesmentioning
confidence: 99%
“…Twenty-seven SNVs had been previously annotated and three of them were novel variants. We also used LOD scores derived from WES-common SNVs to reduce the list of candidate variants, as previously described ( Gazal et al, 2016 ), and 10 candidate variants remained (Supplementary Tables S1 , S2 ). The selected candidate variant, a missense heterozygous variant in the coding regions of ELF2 [NM_201999.2], that segregated with the phenotype was validated by Sanger sequencing.…”
Section: Introductionmentioning
confidence: 99%